THEORETICAL APPROACHES TO LOCAL DEVELOPMENT IN THE CONTEXT OF RURAL AREAS - Maciej Stawicki (Acta Scientiarum Polonorum. Oeconomia, 2018)
The aim of the work is to make a synthetic review of definitions of regional and local development in economic terms in relation to rural development. Rural development is a topic often taken up in scientific research by sociologists, geographers and economists, but it is not defined in a specific way, and is usually understood as development in relation to rural areas. Therefore, the paper presents an overview of various approaches to local development and regional development, using the method of literature studies. The work has reviewed many approaches, features and definitions of socio-economic development as well as regional and local development, which also refer to rural areas and finally proposed a place for rural development in regional and local development.